Abnormal left heart function after operation for atrial septal defect. - Davies, H (1970)
Post-operative data have been presented in seven patients with atrial septal defect. In five of them, residual patency of the atrial septum was found at cardiac catheterization, but in two the defect had been closed. All showed evidence of 'left-sided dysfunction', expressed either as an increase in the pulmonary arterial wedge pressure or the left ventricular end-diastolic pressure or both. The reasons for these findings are not clear, though in several there were indications of impaired right ventricular compliance and possible transmission of raised right-sided pressures to the left side of the heart through a still patent atrial septum. This could not, however, be the mechanism in all cases, and dysfunction of the left ventricle has been seen in two patients in whom the defect was securely closed. The cause of this phenomenon in these selected cases remains obscure.